Networking: enabling professional development and institutionalisation of environmental education courses in Southern Africa - Lupele, Justin Kalaba (Rhodes University, Faculty of Education, Department of Education, 2007)
This study was aimed at understanding how networking can enable or constrain professional development and institutionalisation of environmental education courses in southern Africa in the context of the Course Development Network (CDN), a project of the Southern Africa Development Community Regional Environmental Education Programme (SADC REEP). The study involved 12 institutions (each institution was represented in the CDN by a staff member) in eight SADC member states. It was contextualized through a review of social, political, environmental and educational developments in southern Africa, with specific reference to regionalization processes, as the SADC REEF is constituted under this post-colonial political framework. Relational philosophy informed the research process and methodology. The philosophy underpinned three distinct, yet related theoretical perspectives namely: critical realism, which provided the ontological perspectives of the study; Actor Network Theory; and Community of Practice, which provided the epistemological perspectives. Data was generated during a 33-month period in southern Africa and 12 months in the United Kingdom (and on a one week visit to Italy). During a 12 month Split Site Commonwealth Scholarship award, tenable at Manchester Metropolitan University in the United Kingdom, I studied the Environment and School Initiative (ENSI) and the Sustainability Education for European Primary Schools (SEEPS), to examine whether the same mechanisms that made them successful would apply to the CDN in the context of southern Africa. While these two case studies provided useful insight into the relationship between networking, professional development and institutionalization of environmental education programmes, they were not the main focus of the research. Data analysis was mainly through inductive, abductive and retroductive modes of inference. Inductive data analysis was done by means of Nvivo "“ a computer software package used for qualitative data analysis. The software aided in revealing features and relationships in the data in more depth as it allowed flexibility in working with data. Abduction is the interpretation of a phenomenon by means of a conceptual framework. In this study, I used Actor Network Theory (ANT) (Latour & Woolgar, 1979; Callon, 1986) and Community of Practice (COP) (Lave, 1988; Lave & Wenger, 1991; Fullan, 2003) as analytical conceptual frameworks to probe networking and professional development respectively. Data on institutionalisation of environmental education courses was analysed by means of retroductive mode of inference, which is a thought operation that enables the understanding of social reality beyond what is empirically observable or experienced. This study reveals that there were a number of necessary (internal) and contingent (external) factors that enabled or constrained networking, professional development and institutionalisation of environmental education courses in the context of the CDN. The key factors included existing cultural capital, donor political economy, power relations, poverty related factors and social transformation trends. The study found that relational approaches and the use of three relational theoretical lenses provided a broader lens which enabled this study to identify different dynamics, greater ontological depth and understanding of the relational dynamics and relations at play in the CDN beyond the participants' experience and observable events. The study also contends that networking can provide a support structure for social transformation and change in environmental education.
Keywords: SADC Regional; Environmental Education Programme; Education -- Africa, Southern; Environmental education -- Africa, Southern; Environmental education -- Study and teaching -- Africa, Southern